EVALUATING THE EFFECTIVENESS OF SOCIAL PROTECTION IN REDUCING STUNTING IN INDONESIA - Damanik, Mario; Rachmawati, Rika Reviza; Mufidah, Lyli; Malik, Farmawaty; Lestari, Esta (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: Social protection programs constitute sensitive interventions addressing the underlying causes of stunting. However, empirical evidence regarding the extent to which social protections contribute to reducing stunting remains inconclusive. Aims: This study examines the correlation between social protection programs and the incidence of stunting in Indonesia, utilizing data from the 2022 Survey of the Nutritional Status of Indonesian (SSGI) with a sample size of 323,887 children aged 3 to 60 months. Methods: The study employed binary logistic regression, with childhood stunting incidence as the dependent variable. This method enables the estimation of the probability of stunting based on variations in program exposure. The key programs of interest are Program Keluarga Harapan (PKH), Bantuan Langsung Tunai (BLT), Bantuan Pangan Non-Tunai (BPNT), and Wilayah Prioritas Stunting (DPS), incorporating other control variables related to child, household, and household infrastructure characteristics. Results: BLT is positively associated with stunting, while PKH, BPNT, and DPS show no significant effects. Conversely, access to clean water, sanitation, and clean cooking energy reduces stunting, underscoring the role of health-related infrastructure and the limited contribution of social protection programs to child nutrition. Conclusion: In a policy perspective, the findings underscore the need for greater harmonization between social assistance programs and broader improvements in health, nutrition, environmental conditions, targeted education, health behaviour towards improved nutritional intake, and healthy practices. A novel contribution of this study is offering one of the largest nationally representative analyses linking multiple social protection programs (PKH, BPNT, BLT, and DPS) to stunting outcomes using SSGI 2022 data at the individual level.  Keywords: Stunting, Family Hope Program (PKH), Direct Cash Transfer (BLT), Non-Cash Food Assistance (BPNT), Stunting Priority Areas (DPS).